Triaxial tension and compression tests on saturated lime-treated plastic clay upon consolidated undrained conditions - Kuchvichea Kan; Bertrand François (Journal of Rock Mechanics and Geotechnical Engineering, 2023)
Lime-treatment of clayey soil significantly increases its shear and tensile strengths. Consequently, the tensile strength of lime-treated soils deserves careful investigation because it may provide an appreciable benefit for the stability of earth structures. This study investigates the tensile and shear strengths of an untreated and lime-treated (3% of lime) plastic clay at different curing times (7 d, 56 d and 300 d), through triaxial tension and compression tests. Triaxial tension tests are performed using “diabolo-shaped” soil samples with reduced central section, such that the central part of the specimen can be under axial tension while both end-sections remain in axial compression. Consolidated undrained (CU) conditions with measurement of pore water pressure allow analyzing the failure conditions through effective stress and total stress approaches. The results of triaxial tension tests reveal that the failure occurs under tensile mode at low confining pressure while extensional shear failure mode is observed under higher confining pressure. Consequently, a classical Mohr-Coulomb shear failure criterion must be combined with a cut-off tensile strength criterion that is not affected by the confining pressure. When comparing shear failure under compression and tension, a slight anisotropy is observed.